Field Test of an Epidemiology Curriculum for Middle School Students - Kaelin, Mark A. (2007)
The purpose of this study was to test the effectiveness of a middle school epidemiology curriculum called Detectives in the Classroom. The curriculum presents epidemiology as the science of public health, using health-related issues that capture the interest of young students and help prepare them to make evidence-based health-related decisions. The curriculum was field tested among seventh-grade urban students using a quasi-experimental design. Analysis of covariance of pre- and post-test scores examined five outcomes, including students' perceptions of their abilities in science as inquiry, scientific literacy, and knowledge about five enduring epidemiologic understandings; their self reported interest in science, and assessment of students' epidemiological reasoning ability. The 378 experimental students, compared to 620 controls, had generally higher post-test improvements in epidemiology-related outcomes and smaller increases in the other measures. A dose-response was suggested by higher scores among students exposed to more than 10 lessons. Strengths of this evaluation include a large sample and availability of data to account for differences in demographic and school performance variables. Limitations of this evaluation include randomization by school as opposed to student, the relatively short-term and generally self-reported outcomes, and inconsistencies in proportion of the curriculum actually taught. The findings offer encouragement about the potential for Detectives in the Classroom to improve students' perceptions of their science abilities and scientific literacy, their interest in science and their abilities in basic epidemiologic reasoning. Further tests of this and other epidemiology curricula are needed to respond to the growing interest in teaching public health science to younger students. And while it is important to test near-term impacts, an additional challenge from a curriculum evaluation standpoint will be to follow students over several years to examine subsequent choices concerning selected courses, college majors, and career paths.